Feasibility of drugs in Brugada syndrome - El-Battrawy, Ibrahim; Borggrefe, Martin; Lang, Siegfried; Zhou, Xiao-Bo (Europace, 2018)
The article by Kamkura et al.1 published in Europace describing the feasibility of long-term use of beta-blockers (BB) and calcium antagonists (CA) in Brugada s
Gesehen am 22.08.2019